Prescribing Pattern of Antihypertensive Medications in a Geriatric Center In South Western Nigeria (2019)
Background: Hypertension is a prominent public health problem, with considerable health consequences. Recommended guidelines encourage use of antihypertensive medications with the best evidence of reducing cardiovascular risk. Data on antihypertensive medications use among older Nigerians is limited. Objective: This study evaluated the antihypertensive medication use among older persons with hypertension in compliance with the Eighth Joint National Committee guidelines (JNC 8). Method: A retrospective cross-sectional study, of older patients diagnosed with hypertension between the 1st January 2017 and 31st December 2017 at the geriatric center, University College Hospital, Ibadan. Results: The mean age was 70.2 ± 7.2 years and 62% were female. The mean number of medications used by the patient was 4.5 ± 1.4. Of the patients, 56% were receiving combination therapy, 42% two drugs and 14% three drugs. Most patients were receiving calcium channel blockers (33.8%), followed by diuretics (29.6%), angiotensin receptor blockers (23.4%) and angiotensin-converting enzyme inhibitors (10.8%). Commonest combination therapy was calcium channel blockers and thiazide diuretics (28.3%), while the commonest multi-morbidities were osteoarthritis (32.7%), diabetes (17.3%) and dyslipidemia (8.7%). Conclusion: This study showed that more than half of older persons with hypertension were on combination therapy, and the most frequently used class of antihypertensive drugs were calcium channel blockers, followed by diuretics. The guidelines and data for black ≥60 years indicate that lower doses of combination therapy are more effective in achieving blood pressure target. Despite the numerous advantages of ACEIs, they remain underutilized.